Influence of coating ligands on enzyme-linked immunosorbent assay of toluene - Kim, SY; Lee, NT; Choi, MJ (WILEY-V C H VERLAG GMBH, 2001)
The specificity of conjugation site for coating ligands was investigated using toluene-bovine serum albumin (BSA) conjugates in which BSA was conjugated at the position of o-, m-, and rho -toluic acid. Toluene-BSA conjugated at rho -position showed a binding activity of about 89-95%, whereas, those conjugated at o- and m-position of toluene exhibited a binding activity of 5 and 11%, respectively. On the basis of the above result, coating ligands with various proteins (OVA, BSA, KLH) were compared by conjugating with p-toluic acid, and toluene-KLH was considered as the best coating ligand for this ELISA. Indirect competitive ELISA method was developed using anti-toluene antibody and rho -position conjugated toluene-KLH. The dose-response curve constructed after kinetic and optimization studies showed a 1 x 10(-4)-1 x 10(2) mM detectable response range with 0.1 muM detectability. In specificity test of the antibody, the binding capabilities of aromatic compounds substituted with nitro-, alkyl-, chloro-, and hydroxyl group were larger rather than those of aromatic compounds (benzene, toluene and xylene) themselves. Also, tests with soil and water samples that had been spiked with toluene resulted in 102.7-113.7% recovery.
Keywords: DIGOXIN ANTIBODY; IMMUNOASSAY; IMMUNOSTRIP